Impact assessment: smallholder coffee agronomy and Postharvest trainings in the highlands of Papua New Guinea - Kepa, Leo Aroga (Curtin University, 2015)
The study examined the impact of trainings on coffee farmers in PNG looking at needs, processes and outcomes. One hundred smallholder farmers were randomly selected from six groups. The training programs were found to be suitable in facilitating acquisition of required knowledge; however, training needs analysis and follow-up exercises were not necessary as farmers were able to learn without them. The key impediment to innovation adoption was lack of price incentives for quality.